1993
DOI: 10.1021/j100120a027
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal cationization of laser desorbed perfluorinated polyethers with FTICR mass spectrometry

Abstract: Mass spectra of perfluorinated polyether (PFPE) films on metal substrates have been measured using a novel transition-metal cationization technique combined with FTMS. Full parent mass distributions were obtained with this technique. Two pulsed lasers were employed: a low fluence laser for PFPE desorption and a high fluence laser for metal ion formation. Cationization was observed to occur in the gas phase above the sample surface. The dynamics of the process are discussed. Applications to measure average mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…An essentially identical pattern has been reported previously in an experiment in which Demnum-S was desorbed from a metal surface with one laser, while a second laser was applied to generate low-energy photoelectrons from the metal substrate, and the resulting ions were examined by an ion cyclotron mass spectrometer . The similarity of the cited pattern to that presently observed strongly supports the contention that the negative ion TOF-SIMS spectra of PFPEs are dominated by anions produced by dissociative capture of low-energy electrons.…”
Section: Resultssupporting
confidence: 83%
“…An essentially identical pattern has been reported previously in an experiment in which Demnum-S was desorbed from a metal surface with one laser, while a second laser was applied to generate low-energy photoelectrons from the metal substrate, and the resulting ions were examined by an ion cyclotron mass spectrometer . The similarity of the cited pattern to that presently observed strongly supports the contention that the negative ion TOF-SIMS spectra of PFPEs are dominated by anions produced by dissociative capture of low-energy electrons.…”
Section: Resultssupporting
confidence: 83%
“…Lignins, the cell wall constituents of wood, produced negative ions up to mlz 3000, and spectra confirmed the existence of stable trimer building blocks. Cromwell et al (1993) examined perfluorinated polyether (PFPE) films on metal substrates using a dual-pulsed laser system. A low fluence laser was used for sample desorption, and a second higher power laser ablated the underlying metal substrate to promote cationization in the gas phase.…”
Section: Polymer Studiesmentioning
confidence: 99%
“…Substrates ranging from glass, graphite, stainless steel, to other metals can be used in laser desorption to decrease the internal energy of analyte molecules, thereby reducing their fragmentation by an order of magnitude It has recently been reported that noble transition metal ions produced in the gas phase by laser ablation of a metal probe tip or a metal-substituted zeolite can act as chemical ionization (CI) reagents for analyte molecules, with minimal fragmentation. , …”
mentioning
confidence: 99%